The chemical composition of polyphenolic compounds Achillea micranthoides Klok. herbs - I. F. Duyun; O. V. Mazulin; G. V. Мazulin; Т. V. Oproshanska (The State Expert Center of the Ministry of Health of Ukraine, 2020)
For obtain modern herbal remedies, medicinal plants containing flavonoids and hydroxycinnamic acids are promising. These polyphenolic compounds are characterized by structural diversity, non-toxicity, a wide range of pharmacological activity. An actual problem is the development of new modern instrumental research methods. In scientific and folk medicine the genus Achillea L. of the Asteraceae L. family are widely used to accelerate wound healing, stop bleeding of various etiologies, as anti-inflammatory and anthelmintic agents. The herb of Achillea micranthoides Klok. has theoretical and practical interest. The plant is distributed in the southern regions of the Black Sea and Mediterranean countries, Europe, Ukraine. A long growing season contributes to the accumulation of biologically active polyphenolic compounds from groups of flavonoids and hydroxycinnamic acids. The aim of the work was to study the composition of polyphenolic compounds (flavonoids and the hydroxycinnamic acids) in the herbs of the Achillea micranthoides Klok. during flowering (june-september). The object of research was herb of Achillea micranthoides Klok. Harvesting was carried out in south and oust regions of Ukraine during flowering (June-September, 2017). The investigation of polyphenolic compounds were performed by TLC and HPLC methods. HPLC analyzes were performed using an Agilent Technogies (Model 1100) (Japan). The chromatographic column ZORBAX-SB C-18 measuring 2.1×150 mm, filled with octadecylsilyl sorbent, with a grain diameter of 3.5 microns were used. The systems as the mobile phase: trifluoroacetic acid 0,2%, methanol anhydrous and a mixture of trifluoroacetic acid 0,2% with methanol 70% were used; wave length 313 nm, 350 nm. During the flowering period, the presence and quantitative content were established 8 flavonoids (up to 1,176 ± 0,122%) and 6 hydroxycinnamic acids (up to 0,807 ± 0,071%). The identified flavonoids are dominated by compounds: apigenin-7,4'-di-O-glucoside, quercetin-3-O-rutinoside, luteolin-6-C-glucoside, luteolin-7-O-β-D-glucopyranoside, apigenin-7-O-β-D-glucopyranoside. The highest content in the composition of hydroxycinnamic acids was found for chlorogenic and caffeic acids. The obtained results to be used for perspective modern herbal remedies from Achillea micranthoides Klok. herb with anti-inflammatory, antioxidative, haemostatic and hepatoprotective activities. The qualitative and quantitative determination methods of polyphenolic compounds in Achillea micranthoides Klok. herb may be used to the State Ukraine Pharmacopoeia monographs.